Analisis Keberhasilan Reklamasi berdasarkan Keputusan Menteri Energi dan Sumber Daya Mineral Nomor 1827 Tahun 2018 pada Lahan Bekas Tambang Air Jelitik 3 PT TIMAH Tbk Kabupaten Bangka - Guskarnali Guskarnali; Regita Kasih Parenty; Delita Ega Andini (MINERAL, 2019)
PT Timah Tbk is a mining industry company which produces the tin metal. A mining former area which is chosen as the research location is Lahan Air Jelitik 3. This research aims to analyze the success of Lahan Air Jelitik 3’s reclamation based on Matrik 16 and Matrik 17 of Keputusan Menteri Energi Sumber Daya Mineral Nomor 1827 Tahun 2018. The research starts with collecting the primary data which consists of 43 and 29 coordinate points of Lahan Air Jelitik 3’s adjustment and revegetation, the length and width of 22 erosion in Blok 1, 24 erosion in Blok 2 and 4 landslide in both blocks, the height and diameter of 35 primary plants and the length of 5 cover crops. Those primary data and secondary data are processed by calculating the broad realization of Lahan Air Jelitik 3’s adjustment and revegetation, the amount of plants, the average of plant’s height and diameter, the stability of area and valuating the success of adjustment area, the success of revegetation, the success of last completion based on Matrik 16, also calculating the success reclamation value based on Matrik 17. The result of data processing shows the success value of adjustment and hoard area is 0.5, top soil’s spreading is 0.91, erosion and sedimentation’s control is 0, cover crop’s revegetation is 0.86, fast growing plant’s revegetation is 0.1765, local plant’s revegetation is 0.726, acid mine drainage’s management is 0, plant’s closure is 0.1059 and plant’s maintenance is 0.333. The reclamation’s success percentage 50.65% in Lahan Air Jelitik 3 PT Timah Tbk shows that the reclamation in that area is not good enough and the area needs improvement especially in plant’s maintenance, erosion and sedimentation’s control and acid mine drainage’s management.